HUBUNGAN ANTARA STATUS GIZI DAN KONSUMSI JUNKFOOD DENGAN MENARCHE DINI PADA SISWI SMPN 13 GRESIK DI KECAMATAN UJUNGPANGKAH KABUPATEN GRESIK - yumni, fathiya luthfil (Sinar : Jurnal Kebidanan, 2023)
Korespondensifathiya@i2dot.net Keywords: Early Menarche, Early Adolescence Objective: Early adolescents will experience the stage of puberty. Puberty experienced by adolescent girls is marked by the occurrence of menarche. Over time, the age of adolescent menarche in Indonesia has decreased or is called early menarche. The timing of menarche can be influenced by several factors. The purpose of this study was to analyze the relationship between nutritional status and consumption of junk food with early menarche in female students of SMPN 13 Gresik in Ujungpangkah District, Gresik Regency.Methods: This study used a cross sectional analytic research design. With a total population and a sample of 66 respondents were taken using the Total Sampling technique. The dependent variable is nutritional status and consumption of junk food, while the independent variable is early menarche. The research instrument used is a questionnaire via google form. This study was analyzed using the Spearman Rank Correlation Test.Results: The results of the Spearman Rank Correlation Test showed a relationship between nutritional status and early menarche p=0.000, consumption of junk food with early menarche p=0.008.Conclusion: There is a relationship between the factors that cause early menarche in students of SMPN 13 Gresik, Ujungpangkah District, Gresik Regency. Therefore, the school and teachers are able to teach and provide deeper information to students about puberty and nutrition to increase students' knowledge about the importance of knowing things related to puberty.